Information search behavior of European tourists visiting Mauritius - Ramkissoon, Haywantee (Array, 2008)
Summary: Understanding the information search behavior of travelers is important for providing effective marketing strategies and appropriate communication campaigns. Indeed, investigating and understanding such behaviors of tourists have a long tradition in tourism research. Using data collected from 877 respondents, this study analyzes the information search behavior of European tourists visiting Mauritius. The impact of nationality and prior product knowledge on the external information search behavior of travelers has been investigated. Data was collected between September 2006 and January 2007 using structured questionnaires. The analysis was conducted using the Kruskal-Wallis test to analyze the influence of nationality on the use of external sources of information. A series of one-way ANOVA and t-test were also conducted to investigate the relationship between prior product knowledge and use of external sources of information. Results indicate that nationality and prior product knowledge influence travelers' information search behavior. Findings also indicate that for both first-time and repeat visitors, the Internet was an important source of information. However, travel agencies, friends and relatives, information leaflets and National Tourism Offices were found to be more important sources of information for first-time travelers than repeat visitors. The results also suggest that different marketing and communication strategies are necessary to effectively target consumers from the diverse European countries. In conclusion, recommendations for destination marketers in Mauritius are discussed. These include developing close contacts and good relationships with travel agencies, increasing online marketing techniques, encouraging positive word-of-mouth and increasing attention to tourists' satisfaction amongst others. Some limitations of the research are also discussed